Supply-Side Readiness of Primary Health Care in the Bangsamoro Autonomous Region in Muslim Mindanao - World Bank (World Bank, Washington, DC, 2019)
The Philippines has made remarkable progress in the last decades in improving its health outcomes. However, performance is still poor compared regionally and with similar economies. This report was developed with the aim of informing health policy during the political transition from the Autonomous Region in Muslim Mindanao (ARMM) to the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). This transition began with the ratification of the Bangsamoro Organic Law (BOL) in January 2019. This report provides an overview of the current capacities and challenges facing the public primary health care system as the BARMM government enters into its new role. By providing a detailed look at the availability of inputs needed to deliver priority services, it highlights current strengths, and also indicates areas that need to be strengthened if the national and subnational health goals are to be realized. Historically, health outcomes have been far worse in BARMM than elsewhere in the country. While health outcomes are complex and multi-dimensional, weaknesses in health governance have exacerbated the geographic and socio-cultural challenges associated with health care delivery. While the authors recognize that the transition is likely to introduce some challenges, it is hoped that the findings documented in this report can guide health policy, including investments towards high-impact priorities and in this way, help lay the foundation for better health care, and better health for the people of BARMM.